2009
DOI: 10.1021/ja809165h
|View full text |Cite
|
Sign up to set email alerts
|

Local Membrane Mechanics of Pore-Spanning Bilayers

Abstract: The mechanical behavior of lipid bilayers spanning the pores of highly ordered porous silicon substrates was scrutinized by local indentation experiments as a function of surface functionalization, lipid composition, solvent content, indentation velocity, and pore radius. Solvent-containing nano black lipid membranes (nano-BLMs) as well as solvent-free pore-spanning bilayers were imaged by fluorescence and atomic force microscopy prior to force curve acquisition, which allows distinguishing between membrane-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(203 citation statements)
references
References 27 publications
16
185
0
2
Order By: Relevance
“…51,52 Depending on the surface of the porous supports, the bilayer is formed via the rupture of large or giant unilamellar vesicles and painting of lipids dissolved in organic solvent (Figure 4a). 53 Such configurations are similar to the black lipid membrane in which planar lipid bilayers are formed across Teflon apertures with hole diameters of 0.1-1 mm. In contrast to the black lipid membrane, the substantially reduced pore size gives the resulting lipid bilayers long-term stability and compatibility with the automated and miniaturized electronic devices.…”
Section: Lipid-1d-nanostructure Hybridsmentioning
confidence: 79%
See 1 more Smart Citation
“…51,52 Depending on the surface of the porous supports, the bilayer is formed via the rupture of large or giant unilamellar vesicles and painting of lipids dissolved in organic solvent (Figure 4a). 53 Such configurations are similar to the black lipid membrane in which planar lipid bilayers are formed across Teflon apertures with hole diameters of 0.1-1 mm. In contrast to the black lipid membrane, the substantially reduced pore size gives the resulting lipid bilayers long-term stability and compatibility with the automated and miniaturized electronic devices.…”
Section: Lipid-1d-nanostructure Hybridsmentioning
confidence: 79%
“…The mechanical behaviors of pore-spanning lipid bilayers were scrutinized by local indentation experiments with an atomic force microscopy tip (Figure 4c). 53 The responses of the membranes were fully elastic, but the origins of these linear responses were varied depending on the preparation method and lipid composition. …”
Section: Lipid-1d-nanostructure Hybridsmentioning
confidence: 99%
“…Ursell et al (13) observed a repulsion of domains in deflated GUVs, caused by the induction of membrane curvature between the l o domains. In the case of PSMs, the rather large lateral membrane tension of about 1 mN·m −1 (23,24,32) prevents the induction of a 3D structure in the center of the PSM, although it does not significantly alter phase separation (33,34). This trait allows the l o domains to merge, leading to only one mobile domain in each PSM.…”
Section: Resultsmentioning
confidence: 99%
“…This is presumably a result of the fact that pore-spanning membranes are already pre-stressed even before lipids are removed. [21] The prestress facilitates their rupture if the cholesterol surface concentration is reduced. This observation is different from what has been reported by Giocondi et al, [22] who found stable holes in solid supported membranes upon lipid depletion, which indicates the minor mobility of the lipids on the support.…”
Section: Modulation Of the Phase Separation In Pore-suspending Membranesmentioning
confidence: 99%